2012
DOI: 10.1212/wnl.0b013e3182535d35
|View full text |Cite
|
Sign up to set email alerts
|

Total daily physical activity and the risk of AD and cognitive decline in older adults

Abstract: A higher level of total daily physical activity is associated with a reduced risk of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
438
4
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 589 publications
(490 citation statements)
references
References 30 publications
25
438
4
11
Order By: Relevance
“…Much of the evidence for a beneficial role of exercise in AD patients is associative in nature and based on self-reporting of physical activity levels by participants. Despite this shortcoming, it has been consistently reported that exercise is associated with a reduced risk of dementia and the level of reported physical activity correlates with the incidence of dementia across a number of studies (Andel et al, 2008;Buchman et al, 2012;Larson et al, 2006;Ravaglia et al, 2008). Randomised controlled trials, although few in number, also support exercise as a pro-cognitive intervention in individuals diagnosed with dementia (de Andrade et al, 2013;Kemoun et al, 2010;Van de Winckel et al, 2004;Venturelli et al, 2011;Vreugdenhil et al, 2012).…”
Section: Exercise In the Clinicmentioning
confidence: 99%
“…Much of the evidence for a beneficial role of exercise in AD patients is associative in nature and based on self-reporting of physical activity levels by participants. Despite this shortcoming, it has been consistently reported that exercise is associated with a reduced risk of dementia and the level of reported physical activity correlates with the incidence of dementia across a number of studies (Andel et al, 2008;Buchman et al, 2012;Larson et al, 2006;Ravaglia et al, 2008). Randomised controlled trials, although few in number, also support exercise as a pro-cognitive intervention in individuals diagnosed with dementia (de Andrade et al, 2013;Kemoun et al, 2010;Van de Winckel et al, 2004;Venturelli et al, 2011;Vreugdenhil et al, 2012).…”
Section: Exercise In the Clinicmentioning
confidence: 99%
“…Während Studien, die auf eine direkte pharmakologische Beeinflussung der Demenz zielten, in den letzten Jahren nahezu vollständig enttäuscht haben -so zuletzt bezüg-lich des Antikörpers Solanezumab [3] bieten sich aus der präventiven Perspektive vielversprechende Ansätze. Sowohl epidemiologische Studien als auch Interventionsstudien zeigten auf, dass sich Bewegung und ein gezieltes Kraft-und Ausdauertraining im mittleren Erwachsenenalter positiv auf die Kognition im Alter auswirken [4,5] und auch die Wahrscheinlichkeit, an einer Demenz zu erkranken, senken [6,7]. Wenn bereits ein "mild cognitive impairment" [8] oder eine Demenz [9] Noch befinden wir uns erst am Anfang in unserem Bestreben, Menschen mit Demenz in ihrem jeweiligen Umfeld angemessen zu begegnen.…”
Section: Menschen Und Demenzunclassified
“…54 Furthermore, it is well established that CVRF-reducing lifestyle habits during early and mid-adulthood, including physical exercise and dieting, may reduce the risk of cognitive deficits and AD later in life. [56][57][58] Moreover, several studies have indicated that cognitive impairment may be present in individuals suffering from other cardiovascular conditions such as congestive heart failure (CHF), [59][60][61] atrial fibrillation (AF), 62,63 and coronary artery disease. [64][65][66] Such cognitive deficits may be reduced by stabilization of the cardiac condition.…”
Section: Cardiovascular Risk Factors and Cognitive Declinementioning
confidence: 99%